A QUALITATIVE EXPLORATION OF THE KNOWLEDGE, ATTITUDES, AND PRACTICES OF EARLY CHILDHOOD EDUCATION IN NIGERIA (2025)
The study used a qualitative design to explore the knowledge, attitudes, and practices of early childhood education (ECE), held by educators and parents in the city of Ibadan, Nigeria. The study proceeds upon the understanding that early childhood education provides the ground for the progressive lifelong development of a child. It discusses how the different stakeholders perceive, value, and put to practice ECE. The study is anchored to Bronfenbrenner’s (1979) Ecological Systems Theory. Through in-depth interviews of ten (10) educators, and parents, this study identified more nuanced understandings of the extent of awareness on child development theories, qualification depth, and socio-cultural beliefs influencing ECE delivery and participation. Findings show clear differences in understanding and application of ECE principles: on the part of the educators, there is some theoretical knowledge but little adaptation in the classroom, while on the part of the parents, ECE is perceived much as custodial care and not viewed as essentially developmental. Attitudes toward ECE were constructed primarily by socioeconomic realities, educational backgrounds, and exposure to information regarding child development. Practices consisted of a cocktail of traditional methods as well as irregular ones, which were associated with issues of poor training, infrastructure limitations and perceptions from society about early childhood learning. Such results were also substantiated from literature, borrowed from sub-Saharan Africa and Nigeria that shed light on systemic underinvestment, poor teacher preparation, and misconceptions by parents regarding early learning. The study ends by recommending better professional training for educators, mass parental sensitisation, and stronger policy support for ECE implementation. Limitations cover the geographical area the study focused on and the reliance on self-reported data. Future research is recommended to include determining the dynamics of ECE across the regions of the diverse nation of Nigeria, as well as incorporating the voice of the children in future inquiries. This study foregrounds the voices of educators and parents in order to provide context-specific evidence for policy and practice toward improvement in early childhood education in Nigeria. Keywords: Attitude, Early childhood education, Educators, Knowledge, Parents, Practices.